Incapacity Wittgenstein, Anxiety, and Performance Behavior - Golub, Spencer (Northwestern University Press, 2014)
In this highly original study of the nature of performance, Spencer Golub uses the insights of Ludwig Wittgenstein into the way language works to analyze the relationship between the linguistic and the visual in the work of a broad range of dramatists, novelists, and filmmakers, among them Richard Foreman, Mac Wellman, Peter Handke, David Mamet, and Alfred Hitchcock. Like Wittgenstein, these artists are concerned with the limits of language's representational capacity. For Golub, it is these limits that give Wittgenstein's thought a further, very personal significance-its therapeutic quality with respect to the Obsessive Compulsive Disorder from which he suffers.Underlying what Golub calls "performance behavior" is Wittgenstein's notion of "pain behavior"-that which gives public expression to private experience. Golub charts new directions for exploring the relationship between theater and philosophy, and even for scholarly criticism itself.